PERNIKAHAN MELANGGAR MASA IDDAH DI TINJAU DARI PERSEPEKTIF HUKUM ISLAM DAN HUKUM POSITIf - Muhammad Heru Hresnawanza; Taufik (Sekolah Tinggi Ilmu Syariah Abu Zairi Bondowoso, 2023)
Marriage is a sunnah of the prophet that even if it is not recommended, humans in their nature will do marriage themselves. However, keep in mind that every time there is a meeting there must be a separation as well as marriage. So that if there has been a divorce then a woman carries out the iddah time but there are many incidents that do not do that rule so that it needs to be discussed by researchers. This research is a type of field research (field reseach) using qualitative methods. The types and sources of data used are primary data and secondary data, data collection techniques using observation, interviews and documentation. The results of this study are that a woman who has divorced her husband and carried out the iddah period, there are rules that must be avoided by the woman, including not being allowed to remarry, using perfume, and wearing clothes that can cause fitnah.